Kebertahanan Tradisi Meta ,Ua pada masyarakat Buton di Kecamatan Siompu Kabupaten Buton Selatan - Romastian Romastian (JURNAL KABANTI: Kerabat Antropologi, 2022)
This study aims to identify and describe the symbolic meaning of the meta’ua tradition in the Sompu community and why the meta’ua tradition is still maintained by the Siompu community. This research user symbolic theory by Clifford Geertz. The research method used is descriptive qualitative with data collection carried out by observation and in-depth interviews. The results of this study indicate that the symbolic meaning of tools and materials including the meaning of drums, meaning of gongs, shields, long machetes, spears and fraingipani flowers. The meanings of behavioral symbols include the meaning of humaano Baruga (eating together in a traditional house), the meaning of fomani dance and the meaning of aroano rewu (picking up trash). The meta’ua tradition is still maintained by the Siompu community because it has positive values including: the meta’ua tradition can contribute to the life of the Siompu community, especially in realizing social solidarity, as an arena for community gathering, establishing communication between communities, creating mutual cooperation and mutual cooperation. Help each other complete the work a nd there is a sense of shared responsibility in completing the work so that it is still maintained and cultifated.